Congochromis rotundiceps sp. nov., a new cichlid species (Actinopterygii: Cichlidae) from the Congo Drainage - Wingi, Nadine Usimesa; Schedel, Frederic D.b; Schliewen, Ulrich Kurt (Zootaxa, 2022)
A new dwarf cichlid, Congochromis rotundiceps sp. nov., (Cichliformes: Cichlidae) is described from the central Congo basin. It is a species of Congochromis based on the following characters: (1) four pores in the dentary laterosensory canal; (2) absence of a laterosensory canal in the angulo-articular, (3) six pores in the preopercle laterosensory canal; (4) a single tubular infraorbital bone behind the lachrymal; (5) 12 circumpeduncular scales; (6) jaw teeth comparatively robust, unicuspids, not closely spaced; and (7) presence of a small, supraneural bone. Congochromis rotundiceps sp. nov. is distinguished from all other Congochromis species by the combination of the following characters: (1) a larger eye diameter (31.4–35.1% HL), (2) a shorter snout length (29.8–32.7% HL), (3) a shorter upper lip length (29.2–32.0% HL), (4) a shorter lower lip length (26.2–33.6% HL), (5) a shorter lower lip width (27.7–31.2% HL), and (6) a shorter anal-fin length (15.3–16.97% SL). Diagnostic characters were extracted mainly from meristic counts and distance measurements from 326 chromidotilapiine cichlid specimens representing all chromidotilapiine genera and 40 described or undescribed species. The analysis of the complete meristic and distance measurements database allowed the diagnosis of C. rotundiceps sp. nov., but not for diagnostic separation of many other chromidotilapiine genera, species, and lineages. This result highlights the necessity to explore additional characters to elucidate chromidotilapiine cichlid taxonomy further.